PROBLEMATIKA MANAJEMEN PENDIDIKAN - Sulton, Moh (TA'LIMUNA: Jurnal Pendidikan Islam, 2012)
In effort to manage a society or an organization, it is needed an ability to planning, organizing, moving the members and taking care, also supervising or evaluating all of activities in the organization. Now, it is famously called management. It has an important role in human life, because management is a part of human activities that cannot be separated from human life both as individual or as part of society. Thus, management science is a must for human, both as individual or a part of group, even for an organization that in its activities combine human resources to reach some certain goals. In education, the thing that needed is education management, by which an educational institution can achieve its aims and goals.